Web-Based Interactive Learning Multimedia with a Constructivist Approach for Elementary School English Lessons - Tiara Arifah; L. Heny Nirmayani; I Made Tegeh (Jurnal Media dan Teknologi Pendidikan, 2025)
The low English learning outcomes of fourth-grade elementary students due to difficulties in understanding time-related vocabulary highlight the urgency of a developmental study aimed at designing and evaluating the validity, practicality, and effectiveness of web-based Interactive Learning Multimedia with a constructivist approach to improve learning outcomes. The study applies the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) with quantitative and qualitative methods. Subjects were fourth-grade students, with samples for individual, small group, and field testing. Data were collected through expert validation questionnaires (content, design, media), teacher and student practicality questionnaires, and pre- and post-tests. Analysis used descriptive statistics for validity and practicality, and a t-test for effectiveness. Validation scores reached 100% (content and media experts) and 96% (design expert). Practicality scores were 98% (teachers) and 95.11%–97.33% (students). Effectiveness was shown by an increase in average scores from 35.15 to 87.65, supported by statistical significance (Sig. 0.00 < 0.05; tvalue 43.424 > ttable 2.040). The study concludes that ILM is valid, practical, effective, and a promising solution for English learning in the Merdeka Curriculum.